Philippine motion pictures, 1908-1958 a checklist of the first fifty years - Momblanco, Maria Carmencita A.; Vallejo, Rosa M.; Del Mundo, Cloduardo Jr. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1979)
This bibliography covers the first fifty years of motion pictures produced and exhibited in the Philippines, 1908-1958, and included 1,372 films. It lists only feature films, presenting film credits as they were found in printed sources primarily newspapers, weekly magazines, monographs about movies, producers' brochures and lists, and souvenir programs celebrating annual awards which were available at the time of compilation.
Where there are conflicting or differing information particularly regarding film title or credits, data gathered from newspaper sources prevail with the variant information noted.
The bibliography proper is arranged alphabetically by film title giving the producer, date and place of first exhibition together with all the credits and a brief summary or blurb when available. A chronological list based on the date of exhibition of the film follows.
There is a select bibliography of periodical articles dealing with Philippine moving pictures covering the years 1946-1976. Four appendices feature film excellence awards, the Maria Clara Awards, FAMAS Awards, Manunuri ng Pelikulang Pilipino Awards, and other international awards given to outstanding Philippine films.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Moving pictures -- Bibliography. -- Philippines